Health expenditures (total, public and private) and per capita income in the BRICS+T: Panel bootstrap causality analysis - Şerif Canbay; Mustafa Kırca (Journal of Economics, Finance and Administrative Science, 2022)
Purpose - The study aims to determine whether there is a bidirectional causality relationship between health expenditures and per capita income in Brazil, Russia, India, China, South Africa and Turkey (BRICS+T). Design/methodology/approach For that purpose, the 2000-2018 period data of the variables were tested with the Kónya (2006) panel causality test. Additionally, the causality relationships between public and private health expenditures and per capita income were also investigated in the study. Findings According to the analysis results, there is no statistically significant causality relationship from total health expenditures and public health expenditures to per capita income in the relevant countries. Besides, there is a unidirectional causality relationship from private health expenditures to per capita income only in Turkey. On the other hand, a unidirectional causality relationship from per capita income to total health expenditures in China, Russia, Turkey and South Africa and from per capita income to public health expenditures in India, Russia, Turkey and South Africa were determined. Consequently, a causality relationship from per capita income to private health expenditures was found out in Russia and Turkey. Originality/value The variables are tested for the first time for BRICS+T countries, vis-à-vis the period under consideration and the method used.
Keywords: 330; BRICS+T; Economic growth; Panel bootstrap causality analysis; Per capita income; Private health expenditures; Public health expenditures